Z Source Inverter for Photovoltaic System with Fuzzy Logic Controller - Vijayabalan R; S. Ravivarman (Institute of Advanced Engineering and Science, 2012)
In this paper, the photovoltaic system is used to extract the maximum power from sun to get the dc voltage. The output dc voltage is boost up into maximum voltage level by using the SEPIC converter. This converter voltage is fed to Z source inverter to get the AC voltage. The Z source inverter system can boost the given input voltage by controlling the boost factor, to obtain the maximum voltage. PWM technique which is used as to given the gating pulse to the inverter switches. Modified system is very promising for residential solar energy system. In stand-alone systems the solar energy yield is matched to the energy demand. Wherever it was not possible to install an electricity supply from the mains utility grid, or desirable, stand-alone photovoltaic systems could be installed. This proposed system is cost-effective for photovoltaic stand-alone applications. This paper describes the design of a rule based Fuzzy Logic Controller (FLC) for Z Source inverter. The obtained AC Voltage contains harmonics of both odd and even harmonics of lower and higher order. Higher order harmonics are eliminated with the help of Filters. Here the impedance network act as a filter to reduce the lower order harmonics obtained in the system. So with the help of FFT analysis this value is obtained to be 15.82%.DOI: http://dx.doi.org/10.11591/ijpeds.v2i4.335